MODERN ASSORTMENT, PROPERTIES AND PERSPECTIVES OF MEDICAL DRESSINGS IMPROVEMENT OF WOUND TREATMENT - A. V. Mayorova; B. B. Syisuev; I. A. Hanalieva; I. V. Vihrova (Фармация и фармакология (Пятигорск), 2018)
The effectiveness of reparation is now characterized not only in terms of wound healing. The aesthetic result is also of great significance. Besides, it is important to ensure the comfort of medication, in order to combine the optimal therapy and the quality of life of the patient. The aim of the study was the literature review on the effective wound treatment with the help of modern dressings, including their assortment and prospects for improvement. Materials and methods. The materials of the study were reliable literary sources containing information about wounds, pathogenesis, the stages of the wound process and its possible violations; the assortment of modern wound coverings and the composition of biologically active substances that have a pharmacological effect; the results of preclinical and clinical trials and their prospects of use in aesthetic medicine. The research was carried out using the information retrieval and library databases (eLIBRARY, Cyberleninka), technical information. The research methods used in the work are: informational, analytical, descriptive. Results and discussion. As a result of generalization and analysis of modern publications devoted to the effective wound treatment, modern views on the wound process, wound coverings, their assortment and compositions are described. The results of pharmacological tests as well as the properties of biologically active substances and carrier polymers used are also presented. It is noted that the prospective compounds for including with the wound coverings and external drugs affecting the repair process at different stages of the wound process are tizol, bischofite, peptides (1-β-interleukin), ectoin. Conclusion. Thus, it has been established that modern wound dressings and dressings containing the substances of different pharmacological groups are offered for effective therapy: antiseptics, anesthetics, repair stimulators, antioxidants that affect different stages and elements of the wound process. Their use can be required in cosmetology. Improving the composition of wound coverings is relevant. The wound coverings based on biopolymers containing interleukins-1, ectoin, hyaluronic acid, bischofite and tizol are of great interest.